2001
DOI: 10.1007/s003300000805
|View full text |Cite
|
Sign up to set email alerts
|

MR enteroclysis protocol optimization: comparison between 3D FLASH with fat saturation after intravenous gadolinium injection and true FISP sequences

Abstract: The aim of this study was to introduce the true fast imaging with steady-state precession (FISP) sequence for MR enteroclysis and compare it with the already used T1-weighted fast low-angle shot (FLASH) sequence. Twenty-one patients underwent both MR and conventional enteroclysis. The MR enteroclysis examination was performed after administration of an iso-osmotic water solution through a nasojejunal catheter and the following sequences were included: (a) true FISP; and (b) 3D FLASH with fat saturation after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(45 citation statements)
references
References 17 publications
(32 reference statements)
2
40
1
2
Order By: Relevance
“…Similarly, the abdomen can be depicted on fat-saturated 3D gradient-echo sequences in conjunction with the intravenous administration of T1-shortening contrast agents [22]. To be suited for small bowel MRI both sequence types rely on the presence of intestinal contrast for delineation and distension of individual bowel loops [23]. The underlying contrast characteristics call for a distending agent characterized by bright signal on T2-weighted images and dark signal on T1-weighted data sets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the abdomen can be depicted on fat-saturated 3D gradient-echo sequences in conjunction with the intravenous administration of T1-shortening contrast agents [22]. To be suited for small bowel MRI both sequence types rely on the presence of intestinal contrast for delineation and distension of individual bowel loops [23]. The underlying contrast characteristics call for a distending agent characterized by bright signal on T2-weighted images and dark signal on T1-weighted data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the desired contrast properties, water appears to be ideal as an MR contrast agent for delineation of the small bowel [12,23,26,28,29]. To assure adequate small bowel distension, the rapid physiological absorption of water needs to be delayed [29]; thus, suitable additives preventing, or at least delaying the absorption of water are desirable.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this technique enabled better delineation of the diverticular wall. It has been shown that the use of either of these techniques may be useful in the demonstration of bowel pathology (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…The speed and motion insensitivity of the acquisition completely eliminates breathing or peristalsis induced artefacts [17,26]. Unlike the halfFourier technique, intraluminal flow voids do not affect steady-state precession sequences; moreover, selective fat-suppression pulses can be used to increase the luminographic effect and remove ''black boundary'' artefacts caused by magnetic susceptibility [27,28].…”
Section: Mrimentioning
confidence: 99%
“…These T 1 weighted sequences can be acquired as two dimensional (fewer motion artefacts) or 3D (higher spatial resolution) data sets. Their use after intravenous Gd administration permits excellent depiction of the mesenteric vessels and identification of hypervascular bowel walls if coupled with a selective spectral fatsuppression pulse [27,29,30].…”
Section: Mrimentioning
confidence: 99%